PERLIDUNGAN HUKUM PENCIPTA KARYA VISUAL KOMIK ATAS PENGGUNAAN DATABASE OLEH PROGRAM KECERDASAN BUATAN (AI) - Fajrin, Fahlevi Anggara; Ratnawati, Elfrida (Ensiklopedia of Journal, 2024)
Abstract: Visual art is one of the oldest ways for humanity to convey their life stories and the history of their civilization, starting from the drawings made by ancient humans on various cave walls, then the raised reliefs and paintings on the walls of religious temples, Hieroglyphic writings, paintings that emerged during the Renaissance period, and even now humanity still enjoys creating and enjoying stories conveyed through visual art media in the form of photos, videos, 2D and 3D animations, as well as comics. The presence of generative Artificial Intelligence (AI) program increasingly facilitates humans to engage in drawing activities and turn those images into a comic book even if the human lacks drawing skills entirely. However, the presence of comic books whose drawings are assisted by AI programs raises new issues. Generative AI programs such as Midjourney, Stable Diffusion, Bing Image Creator, and the likes can produce images simply by a set of command sentences because the companies that own generative AI programs employ data scraping techniques. When data scraping is performed, all the data available on the internet can be collected in unnumbered quantities, and the data scraping program will not care whether the data is protected by Copyright Law and Personal Data Protection Law or not. Copyright Law and Personal Data Protection in Indonesia themselves still cannot provide adequate protection from said act either, but, from the perspective of Responsive Law theory, there is a possibility that comic books and pages in Indonesia can be protected through the Personal Data Protection Law.Keywords: Artificial Intelligence, Copyright Law. Personal Data Protection Law, Comic Books.